To commemorate an anniversary: from the sex-gender system to queer studies (Anclajes, 2021)
On the anniversary of the journal Anclajes, this article reviews its contributions to issues of the sex-gender system, from the last decade of the 20th century to the most recent queer studies. I point out the integration of these contributions to a growing trend in the field of Humanities, both in central and peripheral countries, and describe the relevance of some of the articles published in the journal.
Keywords: sex-gender; queer; Argentine literature; XXI century